2019
DOI: 10.4187/respcare.06284
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory Capacity and Vital Capacity of Healthy Subjects 9–81 Years of Age at Moderate-High Altitude

Abstract: BACKGROUND: Measurements of inspiratory capacity (IC) and vital capacity (VC) are used to recognize dynamic hyperinflation, but appropriate reference values are required to achieve accurate clinical interpretations. Altitude above sea level is a potential determining factor for lung volumes, including IC and VC. OBJECTIVE: To describe IC and VC for healthy people who live in Mexico City at an altitude of 2,240 m above sea level. METHODS: Healthy subjects ages 9-81 y completed slow spirometry by following 2005 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…In the present study, the MPT in >45-year-olds decreased while that in ≤45-year-olds increased, and statistical significance was seen between the two groups. Cid-Juárez et al 19 has found that vital capacity increases from 9-year-old to 20-year-old, and then decrease while aging. We assumed that medical masks acted as a physical barrier and decreased the vital capacity of healthy participants to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the MPT in >45-year-olds decreased while that in ≤45-year-olds increased, and statistical significance was seen between the two groups. Cid-Juárez et al 19 has found that vital capacity increases from 9-year-old to 20-year-old, and then decrease while aging. We assumed that medical masks acted as a physical barrier and decreased the vital capacity of healthy participants to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to age, it appears that the findings on lung capacity are maintained throughout life. Cid-Juarez et al in 2019 found that inspiratory capacity and forced vital capacity among healthy individuals between 9 and 81 years of age residing above 2240 m elevation presented an enviable increase in these parameters, with the highest peak from 9 to 20 years of age [ 37 ]. Another interesting study this time investigating the effects of acute hypoxia on respiratory parameters among young subjects demonstrated that [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the extremely informative and well-written paper recently published in this Journal by Cid-Juárez and colleagues, 1 in which the authors suggest that inspiratory capacity in healthy people at 2,240 m above sea level was higher than that of previous reports in European and Latin-American subjects of the same height, sex, and age who were at sea level. Their study provided robust reference values for persons who live at a moderate altitude.…”
Section: To the Editormentioning
confidence: 87%
“…Ambient conditions when lung function values were taken are not described in more detail in the study by Cid-Juárez and colleagues. 1 Thus, depending on local conditions, such as altitude, weather, and time of day, and whether measurements were taken indoors or outdoors, a broad range of temperatures are conceivable. Accurately measuring lung function, at any temperature, is of great importance for studies of inspiratory capacity and vital capacity.…”
Section: To the Editormentioning
confidence: 99%